Intracerebral Transplants of GMP-Grade Human Umbilical Cord-Derived Mesenchymal Stromal Cells Effectively Treat Subacute-Phase Ischemic Stroke in a Rodent Model - Noh, Jeong-Eun; Oh, Seung-Hun; Park, In-Hyun; Song, Jihwan (Frontiers in Cellular Neuroscience, 2020)
In subacute and chronic phases of the stroke, there are no therapeutics available at present to promote functional recovery. Human umbilical cord-derived mesenchymal stromal cells (hUC-MSCs) are one of the candidate cell types for treating subacute-phase stroke. The benefits of cell-based therapy largely depend on the migratory capacity of products administered, as well as their potential for engraftment in targeted tissues and paracrine activities. Timing and delivery modes may also influence the outcomes of stem-cell therapy. Still, the functional recuperative effects of differing hUC-MSC delivery modes, about cell replacement and cell-to-cell paracrine activity levels, have yet to be clarified in subacute phases of stroke.This study was conducted to compare the therapeutic effects of various delivery routes when administering Good Manufacturing Practice (GMP)-grade hUC-MSCs in a rodent model of subacute-phase stroke. Cell aliquots (1 × 106) were given to rats as intravenous (IV) injections or intracerebral (IC) transplants 1 week after middle cerebral artery occlusion (MCAo). Transplanted rats were examined up to 7 weeks later using various behavioral tests and immunohistochemical analyses. Most IC-transplanted cells survived for short periods (i.e., <4 weeks after receipt) and gradually disappeared, whereas IV-injected cells were undetectable in the brain at the same time points (i.e., 3 days, 4 weeks, or 7 weeks after injection). Although short-lived, IC-transplanted cells effectively improved behavioral deficits, serving to reduce infarct volumes and glial scar formation, increase subventricular counts of proliferating neuroblasts, and promote cerebrovascular ingrowth in ischemic penumbra regions. IV injection, however, failed to improve behavioral function or histologic parameters during the same 7-week time frame. These findings overall suggest that IC transplantation is preferable to IV injection for delivery of hUC-MSCs during subacute phases of stroke.